Detailed National Accounts, SNA 2008: Non-financial accounts by sectors, annual (Edition 2015) (OECD National Accounts Statistics, 2008)
This dataset comprises statistics on the whole set of financial accounts in terms of production accounts, generation of income accounts, allocation of primary income accounts, use of disposable income account, change in net worth due to saving and capital transfer accounts and acquisitions of non-financial assets accounts. Data is expressed in national currency current prices and is available from 1950 onwards